Semi-field evaluation of the predation of Macrocheles embersoni and Macrocheles muscaedomesticae (Acari: Mesostigmata: Macrochelidae) on the house fly and the stable fly (Diptera: Muscidae) - Azevedo, Letícia Henrique [UNESP]; Borges, Vinícius; Filho, Walter Mesquita; de Campos Castilho, Raphael; de Moraes, Gilberto José (Wiley, 2022)
BACKGROUND: The house fly, Musca domestica L., and the stable fly, Stomoxys calcitrans (L.), are important and harmful organisms. The cosmopolitan house fly is not parasitic, but the adults are annoying and a known vector of several pathogens. The importance of the stable fly has increased in Brazil in the last 40 years, after major changes in sugarcane cultivation practices were implemented, including the widespread application of vinasse (byproduct in sugarcane mills) and the parallel reduction of sugarcane preharvest burning. These changes have favored the development of this fly, which can reach high populations, that can negatively affect cattle and other animals. The control of these flies relies heavily on the use of chemical products, which very often do not provide adequate population reduction. Predatory mites of the family Macrochelidae have been evaluated under laboratory conditions for the biological control of these organisms, especially of the house fly. The objective of this study was to examine the predation capacity of the macrochelids Macrocheles embersoni Azevedo, Castilho & Berto and Macrocheles muscaedomesticae (Scopoli) on the house fly and the stable fly, under semi-field conditions (screen-houses). RESULTS: Reductions of 83 to 90% of the house fly and 66 to 73% of the stable fly populations were observed, with the release of 100 of these predators per square meter. CONCLUSIONS: The number of adults of both fly species was much lower in the units where the predators had been released than in the others. However it is suggested that provisioning and or conserving alternative food sources for these macrochelids, such as free-living nematodes, could further improve biocontrol efficacy.
Keywords: biological control; edaphic predatory mites; Musca domestica; Stomoxys calcitrans